Exploration of (R)-[11C]YH168 as a PET tracer for imaging monoacylglycerol lipase in the brain: from mice to non-human primates - He, Yingfang; Zheng, MingQiang; Gu, Jiwei; Reichert, Lisa; Trimborn, Johannes; Zhang, Hui; Keller, Claudia; Crosby, Mallory; Collin, Ludovic; Heer, Dominik; Pavlovic, Anto; Topp, Andreas; et al. (European journal of nuclear medicine and molecular imaging, 2025)
Purpose The monoacylglycerol lipase (MAGL) plays a pivotal role in modulating the endocannabinoid system and is considered an attractive therapeutic target for diseases in both the central nervous system and periphery. The current study aimed to develop and evaluate a suitable carbon-11 labeled tracer for imaging MAGL in preclinical studies. Methods ( R )-YH168 was synthesized via a multi-step pathway and its half-maximal inhibitory concentration ( IC 50 ) values were measured using an enzymatic assay. Radiosynthesis of ( R )-[ 11 C]YH168 was accomplished by 11 C-methylation via Suzuki cross-coupling of a pinacol boron precursor. In vitro autoradiography was performed using brain tissues from MAGL knockout and the corresponding wild-type mice. The metabolic stability of ( R )-[ 11 C]YH168 in mouse brain and plasma was assessed 5 min after injection. Dynamic PET scans were conducted on anesthetized mice and rhesus monkey. For studies in non-human primates, arterial blood samples were analyzed to obtain the input function for kinetic modeling. Blocking studies with the irreversible MAGL inhibitor PF-06795071 were performed to assess the binding specificity of ( R )-[ 11 C]YH168. Results ( R )-[ 11 C]YH168 was synthesized via Suzuki coupling of the phenyl boronic ester with [ 11 C]CH 3 I in the presence of palladium catalyst. In vitro autoradiography revealed a heterogeneous distribution pattern of ( R )-[ 11 C]YH168 with higher binding to MAGL-rich brain regions in wild-type mouse brain slices compared to that of MAGL knockout mice. Dynamic PET imaging in wild-type and MAGL knockout mice confirmed its high specificity and selectivity in mouse brains. In the rhesus monkey, ( R )-[ 11 C]YH168 displayed good brain permeability. High levels of radioactivity uptake were seen in the cingulate cortex, frontal cortex, cerebellum, occipital cortex, and hippocampus, consistent with MAGL expression. The one-tissue compartment model was appropriate for fitting the regional time-activity curves and provided reliable volume of distribution values across all brain regions. Pretreatment with PF-06795071 (0.1 mg/kg) resulted in almost complete blockade (> 95%) of radioactivity uptake, demonstrating binding specificity of ( R )-[ 11 C]YH168 to MAGL in the non-human primate brain. The regional non-displaceable binding potential follows the rank order of cingulate cortex ~ frontal cortex ~ insula > putamen > temporal cortex > caudate ~ occipital cortex ~ thalamus > nucleus accumbens ~ hippocampus ~ cerebellum ~ globus pallidus > substantia nigra > amygdala. Conclusion ( R )-[ 11 C]YH168 is a promising PET probe for imaging and quantifying MAGL in the brains of mice and non-human primates. This 11 C-labeled tracer holds great potential for translation into human subjects and offers the possibility of performing multiple PET scans on the same subject within a single day.